Exploring Jordanian children and parents' awareness, behavior, and perception of pediatric oral health - Eman Hussein Hammouri; Asem Thabit Mustafa; Taghreed Falah Jaradat; Moa'th Mohammad Ghozlan; Mahmoud Yaseen Bani Salman; Ala' Ahmad Ersheidat; Israa Mohammad Nawasra (BMC, 2024)
Abstract Background To evaluate children's and parents' practice and attitude toward oral hygiene and their knowledge about oral hygiene. Methods This cross-sectional questionnaire-based study was conducted on randomly selected children who were seen in the Pediatric dentistry clinic in different Royal Medical Services hospitals. A modified questionnaire was used to gather information from the child or parents to gather the child's demographic data and evaluate the children's and parents' practice and attitude toward oral hygiene, their knowledge about oral hygiene, information about the parent and family, and oral examination, the questionnaire questions' reliability and validity were assessed by test-retest and Cronbach's Alpha test. Results Three hundred seventy four patients were included, and the average age was 5.06 ± 3.58 SD years. Children's and parents' practice toward oral hygiene was inadequate where the majority (83.3%) brush their teeth occasionally, change their toothbrushes infrequently, apply toothpaste inappropriately, and less than half (47.2%) clean their tongue after teeth brushing. A significant number (73%) of candidates were aware that oral health has a significant role in their general health and can prevent dental problems. Participants agreed that maintaining a healthy mouth is an individual responsibility. The majority of participants came from large family size (the average family members 6.1 ± 1.7 SD) who live below the poverty line. Conclusion Our study demonstrated that awareness of oral health status in children below the age of 12 was poor. Although their oral knowledge was good their attitude and behavior were inadequate. These findings urge the need for expanded, well-organized, preventive educational programs that include school's syllabus, house visits, and hospitals for parents and children alike.